The Service Sector in Asia: Is It an Engine of Growth? - Donghyun Park; Kwanho Shin (Asian Development Bank (ADB), 2012)
The underdeveloped service sector in Asia has the potential to become a new engine of economic growth for developing Asia, which has traditionally relied on export-oriented manufacturing to power its growth. The central objective of this paper is to empirically analyze the prospects for the service sector as a future engine of growth. Our analysis of 12 Asian economies indicates that the service sector already contributed substantially to the region's growth in the past. Furthermore, somewhat surprisingly in light of the difficulty of achieving productivity gains in services, we also find that services labor productivity grew at a healthy pace in much of the region. Overall our analysis provides substantial cause for optimism about the role of the service sector as an engine of growth in Asia. However, some Asian countries where the service sector is currently struggling, such as the Republic of Korea and Thailand, will find it more challenging to develop the sector.
hdl:11540/1257
Keywords: O14; O40; O47; 330; Services; structural change; growth; productivity; Asia; Dienstleistungssektor; Strukturwandel; Produktivität; Asien